The experience of mentorship for three novice teachers in Yukon - Aubichon, Orlanna (Author); Brown, Willow (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2014)
As demands on teachers have become more complex and early-career attrition rates have increased, there has been more emphasis on establishing formal mentorship programs for new teachers. In this study, the author explored mentorship, as experienced by three novice teachers in Whitehorse, Yukon. She compared these narratives, including her own anonymous story, to the mentorship programs described by local program planners or decision makers. Analysis revealed common feelings of anxiety and isolation among these new teachers. Findings may inform decision makers about the need to monitor the actual experience of new teachers when mentorship programs are reviewed and revised. Principals may be encouraged to interact with new teachers more frequently and experienced teachers may be inspired to offer support more freely. New teachers may be alerted to the need to enroll in optional mentorship programs or to build their own informal support networks. --Leaf ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1947314